A Fisher-eye lens on social work reform. (September 2021) - McGrath-Brookes, Michael; Hanley, Joe; Higgins, Martyn
Summary: Mark Fisher's Capitalist Realism, published in 2009, has been recognised as one of the most important contributions chronicling the rise, application and consequences of neoliberalism. However, Fisher's ideas have until now only garnered passing mention in the study of neoliberalism in children and families social work in England, despite there being extensive research, argument and publication on the subject more broadly. This article attempts to rectify this gap and apply Fisher's theory to the recent reforms in children and families social work in England. Findings: The article applies Fisher's commentary on the co-option of language, invoking crisis, bureaucracy and proposing change to implement no change, to the reforms in children and families social work that began with the implementation of Reclaiming Social Work in 2008. Since that time, the original architects of Reclaiming Social Work have gained significant positions of power and influence and been instrumental in introducing neoliberal reforms throughout children and families social work in England. Applications: Through applying the approach and concepts of Mark Fisher, this article concludes that it is possible to determine that the current reforms are, at their core, neoliberal in nature and driven by an ideological imperative to transform children and families social work in England into a neoliberal edifice, with less public sector and state input and oversight and an increase in the influence of 'not-for-profits', charities and international for-profit consultancies.